PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE, PROFITABILITAS DAN LIKUIDITAS TERHADAP PERINGKAT OBLIGASI - Sari, Indah Kusuma; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi, 2016)
This research aimed to test positive influence Good Corporate Governance implementation, profitability and liquidity of the bond rating. The theory used in this research is the stewardship theory, agency theory and signal theory. The population in this study is manufacturing company that issues bonds and listed on the Stock Exchange period 2011-2015. The samples used in this study were 40 companies with sampling purposive sampling technique. The collected data using by non-participant observation method. Data analysis technique used is Logistic Regression. The results of this research showed that the Good Corporate Governance and liquidity positive and significant impact on bond ratings. While profitability does not affect the bond ratings.
Keywords: Good Corporate Governance, profitability, liquidity, bond rating